2003
DOI: 10.1016/s1474-5151(02)00088-9
|View full text |Cite
|
Sign up to set email alerts
|

Women's Health after a First Myocardial Infarction: A Comprehensive Perspective on Recovery Over a 4-Year Period

Abstract: Based on a comprehensive perspective on women's recovery after a first MI, a favorable development of the women's health was observed in the behavioral and emotional conditions while deterioration in the social and working conditions was observed over time. Thus, further efforts are needed in the two latter conditions by means of further studies in combination with greater support from healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The very few longer-term studies have been limited by methodology, the use of mainly generic health status instruments (i.e. SF-12), small sample size, and did not focus on young women (≤55 years), 11, 12, 26, 30-35 thus they do not provide an adequate picture of how younger women, a previously established vulnerable population, recover over time. Third, we were able to demonstrate worse outcomes for women and had, with the male controls, the ability to determine whether there were differences in the magnitude of change over time and at baseline hospitalization for AMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The very few longer-term studies have been limited by methodology, the use of mainly generic health status instruments (i.e. SF-12), small sample size, and did not focus on young women (≤55 years), 11, 12, 26, 30-35 thus they do not provide an adequate picture of how younger women, a previously established vulnerable population, recover over time. Third, we were able to demonstrate worse outcomes for women and had, with the male controls, the ability to determine whether there were differences in the magnitude of change over time and at baseline hospitalization for AMI.…”
Section: Discussionmentioning
confidence: 99%
“…6, 11, 12 This model allows us to examine health status patterns from baseline to 12-months post AMI. We included random effects for the intercept and the slope of time (in which the random effect of the slope of time accounts for the difference in time trend within a patient; and the random effect of the intercept accounts for the effect of the repeated measurements within a patient), respectively 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that successful coping is difficult even a year after an MI [16]. Effective coping following an MI calls for knowledge of the disease and of the desired effects of treatment and medication, as well as resources, a problem-solving attitude, and a sense of personal motivation [717]. In order to participate in all phases of MI care, patients need to be made aware of their right to participate [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to make visible the patients who need the most support and counselling in order to achieve control over their disease. This might help to choose the appropriate interventions to promote the patients' adherence to health behaviour change [912, 14, 17] and to reduce psychological distress in order to improve long-term prognosis and quality of life [7, 8, 1517]. …”
Section: Introductionmentioning
confidence: 99%